Seleção recorrente e expressão da família gênica PvPGIP visando resistência ao mofo branco em feijoeiro - Vasconcellos, Renato Coelho de Castro (2017)
The white mold, caused by the fungus Sclerotinia sclerotiorum (Lib.) de Bary, is a disease with a great impact on the common bean crop, because it limits the production potential and reduces the quality of the seeds and pods. Plant resistance mechanisms are due to physiological resistance and escape mechanisms, which include morphology, upright architecture, canopy porosity and plant precocity. The objectives of this work were to obtain bean progenies with higher levels of physiological resistance to white mold, carioca grain type and upright habit, through recurrent selection; verify the efficiency in the selection of these characters and validate the gene expression of the PvPGIP family for white mold resistance. In the recurrent selection the recombination was performed by the partial or conical diallel scheme, the massal selection was in S0 and the progenies were evaluated and selected until the generations S0: 3 (cycle X) and S0: 2 (cycle XI), together with the most resistants of the IX cycle to estimate the gain with selection. The evaluated characters were resistance to white mold by the straw test method, plant habit and grain type. Recurrent selection allowed gains in the resistance to white mold of approximately 6% per cycle and was efficient to obtain progenies with high resistance to white mold, grains of the carioca type and upright habit, adapted to the conditions of South of Minas Gerais. For the expression analysis of the PvPGIP gene family, 4 lines of common bean were evaluated, 2 lines from the recurrent selection program for white mold (50/5 and 84/6), 1 resistant line not adapted to the Brazilian conditions (Cornell 605) and a susceptible line (Corujinha). Two white mold isolates were used and the expression of these genes being evaluated at 0, 1, 2, 3 and 5 days after inoculation. The less aggressive isolate (UFLA 03) did not present significant difference in the relative expression of any of the analyzed genes, being considered inefficient in discriminating the genotypes. With the most aggressive isolate (UFLA 116) all the genes of the family were differentially expressed, they are related to resistance to white mold and showed an increase up to the third day after inoculation. The two progenies selected presented resistance level similar to the Cornell 605. Therefore, the incorporation of these genes can contribute to further improve the resistance levels of the lines derived from recurrent selection and can be used for the development of molecular markers aiming the assisted selection for common bean resistance to white mold.